Enriching the oral vocabulary of the educable mentally retarded primary level - Socrates, Vera Joy U. 1952-; Sison, Waldetrudes Montojo; Valdes, Matilde M. (1973.)
The study answers the question on how to enrich the oral vocabulary of the educable mentally retarded in the primary level. It attempts to know the learning characteristics of the educable mentally retarded children, the implications of the learning characteristics to the enrichment of the oral vocabulary of the educable mentally retarded children, the objectives of oral vocabulary building for the educable mentally retarded children in the primary level, and the activities and experiences necessary to enrich the oral vocabulary of the educable mentally retarded children.
Vita.
Thesis (Master of Arts in Teaching - Special Education : Mental retardation)--University of the Philippines, Diliman.
Keywords: Language acquisition; English language -- Pronunciation -- Study and teaching (Primary) -- Philippines; Oral communication -- Study and teaching (Primary) -- Philippines; Vocabulary; Children with mental disabilities -- Education (Primary) -- Philippines; Special education -- Philippines